2007
DOI: 10.1093/ndt/gfl836
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine enhances platelet procoagulant activity

Abstract: These observations indicate that the thrombogenic properties of CsA may result from the alteration of lipid organization in platelet plasma membrane, leading to externalization of PS and accelerated thrombin generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
0
23
1
1
Order By: Relevance
“…In our study, there was an immediate and sustained decrease in platelet phosphatidylserine expression after administration of the immunosuppressive dosage of cyclosporine. Our findings are in contrast to the findings reported in a recent study of humans, which demonstrated that cyclosporine increased platelet phosphatidylserine expression . One possible explanation for the different results is that in our study, we evaluated the effects of cyclosporine administered in vivo, whereas the previous study in humans incubated platelets with cyclosporine in vitro.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, there was an immediate and sustained decrease in platelet phosphatidylserine expression after administration of the immunosuppressive dosage of cyclosporine. Our findings are in contrast to the findings reported in a recent study of humans, which demonstrated that cyclosporine increased platelet phosphatidylserine expression . One possible explanation for the different results is that in our study, we evaluated the effects of cyclosporine administered in vivo, whereas the previous study in humans incubated platelets with cyclosporine in vitro.…”
Section: Discussioncontrasting
confidence: 99%
“…Upon platelet activation, phosphatidylserine is exposed on platelet surface membranes and binds to prothrombin, converting prothrombin to thrombin, and enhancing secondary hemostasis . Phosphatidylserine also is expressed during apoptosis of nucleated cells .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcineurin inhibitors cause arteriolar vasoconstriction probably through multiple mechanisms, including upregulation of endothelin and thromboxane and downregulation of vasodilators (such as prostaglandin and nitric oxide). Increased procoagulant activity may also play a role [38][39][40]. A recent experimental study showed that cyclosporine induces increased endothelial release of complement activating microparticles suggesting that blocking complement activation may help to alleviate the condition [41 && ].…”
Section: Calcineurin Inhibitor-associated Thrombotic Microangiopathymentioning
confidence: 99%